Dinamika Vegetasi Mangrove Holosen Daerah Semarang Berdasarkan bukti Palinologi - Setijadi, Rachmad; Suwardi, Suwardi; Suedy, Sri Widodo Agung (Dinamika Rekayasa, 2010)
Palynological evidences (pollen and spores) have been used to study mangrove diversity and vegetation fluctuation at coastal  zone sites at Muktiharja, Kemijen Semarang , province of Central Java. Data was collected in April 2nd to April 17th 2006 following transect method, for sediments sampling used surface subsurface sampling method (depth in 25cm). Pollen preparation used Acetolysis method. The result showed that mangrove forest in the coastal zone of Muktiharja, Kemijen Semarang was dominated by Rhizophoarceae pollen type (included Rhizophora genus : Rhizophora mucronata, Rhizophora stylosa dan Rhizophora apiculata). Vegetation of mangrove forrest in this bay was fluctuated which terrestrial climate was influenced in this mangrove forrest.